Mechanisms of inflammation modulation by different immune cells in hypertensive nephropathy - Hao, Xiao-min; Liu, Yu; Hailaiti, Dilizhawaer; Gong, Yu; Zhang, Xu-dong; Yue, Bing-nan; Liu, Ji-peng; Wu, Xiao-li; Yang, Ke-zhen; Wang, Jun; Liu, Qing-guo (Frontiers in Immunology, 2024)
Hypertensive nephropathy (HTN) is the second leading cause of end-stage renal disease (ESRD) and a chronic inflammatory disease. Persistent hypertension leads to lesions of intrarenal arterioles and arterioles, luminal stenosis, secondary ischemic renal parenchymal damage, and glomerulosclerosis, tubular atrophy, and interstitial fibrosis. Studying the pathogenesis of hypertensive nephropathy is a prerequisite for diagnosis and treatment. The main cause of HTN is poor long-term blood pressure control, but kidney damage is often accompanied by the occurrence of immune inflammation. Some studies have found that the activation of innate immunity, inflammation and acquired immunity is closely related to the pathogenesis of HTN, which can cause damage and dysfunction of target organs. There are more articles on the mechanism of diabetic nephropathy, while there are fewer studies related to immunity in hypertensive nephropathy. This article reviews the mechanisms by which several different immune cells and inflammatory cytokines regulate blood pressure and renal damage in HTN. It mainly focuses on immune cells, cytokines, and chemokines and inhibitors. However, further comprehensive and large-scale studies are needed to determine the role of these markers and provide effective protocols for clinical intervention and treatment.